Sustainable Agriculture & Soil health - Thawakar, G.F. (Journal of Soil and Water Conservation, 2022)
India is an agricultural country from times immemorial. Indian agriculture has been dependent on inherent plant nutrient management system. The nutrients were derived from mineral weathering of the soil particles and decomposition of organic waste, use of compost and manures generated at household level by the farmers themselves. The crop yield per unit of such practice was low but sufficient enough to meet the requirements of the population. However, with the increase in population, foodgrain requirement of the country increased sharply and the nation had to resort to import of foodgrains for its survival. This condition galvanised Planners to devise means by which food grains production could be increased to level where it would meet the increased demands of the population. Accordingly, over the plan periods, the performance of agriculture sector, especially in the field of foodgrain production, has witnessed tremendous growth since independence. From a production level of 50.8 million tonnes in 1950-51, foodgrain production has increased to 191 million tonnes by 1994-95 thus exhibiting a rise of 3.7 times leading the country towards self-sufficiency. The phenomenal success achieved in foodgrain production has been the result of extension of area under irrigation, use of high yielding varieties, increased use of fertilizers and also efficient management of soil and water resources by the farming community.